Solutions by everydaycalculation.com

How to solve x + 1 = 3x - 6? Get the answer and stepwise instruction to solve linear equation in one variable 𝒙.

We have **x** + 1 = 3**x** - 6

First, we move the * x* terms to the LHS and constant terms to the RHS of the equation, inverting the sign on the terms. This is also called transposing method.

Transposition is a faster method and combines the following two steps, were we to solve the equation by:

i) Subtracting 1 from both sides

ii) Subtracting 3**x** from both sides

Therefore, **x** - 3**x** = -6 - 1

or, -2**x** = -7

Next, divide both sides by -2, which is the coefficent of **x**

-2**x**-2 = -7-2

**x** = -7-2 or, **x** = 3.5